(untitled) (Journal of Economic Research & Business Administration, 2016)
The strategy of economic development of Kazakhstan aimed at mac roeconomic stabilization, which meant to reduce the government budget deficit and the consistent implementation of tight monetary and credit pol icy during recovery from the crisis gave a positive result. This article exam ines the dynamics of the main macroeconomic indicators of the economy of Kazakhstan in recent years. The analysis identified the major internal and external factors affecting the development of the domestic economy. Also in this paper we consider inflation dynamics and the analysis of the contribution to inflation of certain goods and services. In this connection the conclusion confirms the fact that countries with developed political and economic institutions tend to have lower inflation compared to econ omies with less developed institutions.